Decoupling evolution of water footprint of energy and its driving factors: Evidence from Northeast China - Liying Cui; Shaoping Li; Hengshuo Zhang (PLoS ONE, 2025)
Energy and water are interlinked and inseparable resources of vital importance to the survival and development of human society. Exploring the relationship between energy and water is of great practical significance for the sustainable development of resources. The uneven regional distribution of energy and water in China has exacerbated energy-related water shortages. Base on the water footprint of energy (WFE), this paper takes Northeast China, the old industrial base, as the research object, and explores the regional distribution characteristics and development trend of WFE, so as to provide quantitative basis for the development of regional energy transformation in coordination with energy and water. This study uses the ISO model and the decoupling model, and analyzes the spatial and temporal changes in the water footprint (WF) of energies and the decoupling effects in Northeast China from the perspective of energy production. The findings show: (1) the WFE grew slowly, and the WF of power gradually exceeded that of fossil energy; (2) the spatial distribution of WFE was unbalanced, with higher WF of fossil energy in Heilongjiang and higher WF of power in Jilin and Liaoning; (3) the decoupling status of WFE from GDP was better than that of WFE from total water consumption. This study also analyzes the driving factors of indicators of water endowment, economic development, energy consumption, environmental governance and life quality, on the WFE based on the Lasso model, and provide policy implications for the coordinated development of energy and water in Northeast China.